PENINGKATAN KEMAMPUAN PEMAHAMAN MEMBACA DENGAN MODEL INTERAKTIF MAHASISWA PRODI PENDIDIKAN BAHASA DAN SASTRA INDONESIA FKIP UNIKAL - Nia Ulfa Martha (LPPM Universitas Pekalongan, 2011)
This study used an experimental approach was implemented in three phases, namely Ability Test Reading Comprehension I, II, and III. The subject of this study is the student A morning class the second semester of Educational Studies Program Language and Literature Indonesia FKIP Unikal. This study variables in the form of interactive models of reading comprehension by answering questions and summarizing exercises. Collecting data on the KMP test I, II, and III using the technique in the form of deeds and nontes tests. Nontes technique used is observation. The results showed an interactive model of reading comprehension by answering questions more effectively exercises used morning A class of students the second semester of Educational Studies Program Language and Literature Indonesia FKIP Unikal to improve reading comprehension. In addition, based on test results KMP I, II, and III as well as observations about the attitudes of students during the learning process shows that the application of interactive models of reading comprehension by answering questions proved effective exercises improve student learning outcomes. Keywords: Improvement, reading comprehension, interactive model.